MEANING, LANGUAGE, DAN THOUGHT REMAJA PENGGUNA FACEBOOK DI INDONESIA - Husen Mony (Jurnal Visi Komunikasi, 2015)
This study departs from phenomena of sexual crime to female teenagers which start from their interactions in Facebook. Its level of analysis was conducted in level, namely micro level in form of textual study, messo level in form of study of actor behaviors (interviews: exploration and inspection), and macro level in form of study of cultural content. Finding of the study they are: (1) micro level, victims tend to divide their personal information openly in Facebook. The actor (Ilham) tended to manipulate his personal data on the account of Facebook; (2) messo level, actions (symbolic) conducted by victims were based on bad relationship (communication) with their mothers, an effort to seek figures of father, promises of prizes of the actor. The actions of the actor were based on the socialization environment (friendship), his perception to female teenagers in Facebook as a sexual object; (3) macro level, there is a gap (skill and knowledge) and technological unconsciousness of the actor, parents are unable to accelerate themselves with the advancement of technology, orientation of educational system which has not touched the aspect of building the students consciousness on technology application in a healthy and positive manner, and law enforcement which has not used symbol and language in Facebook as an evidences. Othe finding namely Facebook (new media) is a neutral medium. There are conditions beyond Facebook such as broken home family which dominantly triggering the sexual crimes on the female teenagers.. Penelitian ini berangkat dari fenomena kejahatan seksual terhadap remaja utrid yang bermula dari interaksi mereka di Facebook. Level analisisnya yaitu, studi teks, studi tindakan utri, studi konteks utrid l (network ecology narrative, wawancara, dan observasi). Temuan penelitian, yaitu: (1) level mikro, korban cenderung membagi informasi pribadinya secara terbuka di Facebook. Pelaku (Ilham) cenderung memanipulasi data diri di akun Facebook (2) level messo, tindakan korban dilatari adanya hubungan (komunikasi) buruk dengan ibunya, upaya mencari sosok ayah, dan iming-iming hadiah dari pelaku. Tindakan pelaku dilatari oleh lingkungan pergaulan (pertemanan) dan persepsinya terhadap remaja utrid di Facebook sebagai objek seksual; (3) level makro, remaja tidak sadar teknologi, orang tua tidak yang gaptek, orientasi utrid pendidikan yang belum menyentuh aspek membangun kesadaran anak didik tentang berteknologi secara sehat dan positif, dan penegakan utri yang belum menggunakan utrid dan bahasa di Facebook sebagai alat bukti. Kesimpulan, Facebook (new media) merupakan medium yang netral. Terdapat kondisi-kondisi ekstra-Facebook seperti keluarga broken home yang dominan menjadi pemicu tindak kejahatan seksual terhadap remaja utrid.